Implementasi Model Penerimaan Teknologi Dalam Mengukur Kepuasan Konsumen [Studi Pada Pengguna BRI Mobile di Bengkayang] - Dewi Yovita; Pramatatya Resindra Widya (Universitas Muhammadiyah Magelang, 2021)
The purpose of this study is to analyze the influencing factors including servis satisfaction which consists of two variable, namely the Perceived Usefulness and perceived easy of use on servis satisfaction of Bank Rakyat Indonesia KCP Bengkayang using the BRI Mobile application (BRI Mobile). The number of samples in this study were 152 respondents. In sampling, researchers conducted by distributing questionnaires to serviss via google form. Data collection techniques are using direct questionnaires and literature study. The instrument test technique is using validity and Reliability tests. The data analysis technique is using quantitative descriptive data analysis. The results of the study through questionnaire data showed that the Perceived Usefulness variable had a positive and significant effect on servis satisfaction. The Perceived Ease of Use variable has a positive and significant effect on servis satisfaction. The limitations of this study are the limited number of respondents and the distribution of questionnaires, so it is recommended to increase the number of samples and not limit the distribution of questionnaires.